CREATIVE THINKING SKILLS OF GRADE XI STUDENTS OF MA NURUL ISLAM LUMAJANG IN SOLVING MATHEMATICS PROBLEMS: ANALYSIS BASED ON THE LEVEL OF ACADEMIC ABILITY - Ariani, Anggiarti Dwi (Mathematics Research and Education Journal, 2025)
Abstract This study analyzes the mathematical creative thinking abilities of grade XI students at MA Nurul Islam Lumajang, focusing on their academic levels. Creative thinking is crucial for addressing 21st-century challenges, especially given the low national mathematics literacy highlighted by the 2018 PISA results. Despite the implementation of the Problem-Based Learning (PBL) model, its effectiveness in enhancing students' mathematical creativity remains suboptimal. Using observation methods alongside teaching activities and documentation, the research involved both teachers and students. Findings indicate that students with high academic ability excel in creative thinking indicators, particularly in flexibility and precision. Conversely, those with medium and low abilities struggle to generate original and detailed solutions. This underscores the need for personalized learning strategies tailored to individual student capabilities to foster mathematical creativity. Approaches such as open-ended question-based PBL are recommended to enhance students' fluency, flexibility, authenticity, and accuracy in creative problem-solving. The results highlight the necessity of integrating adaptive learning strategies to improve the quality of mathematics education at the madrasah level. By focusing on these strategies, educators can better support students in developing essential creative thinking skills necessary for their future success.